PERSEPSI SISWA TERHADAP KOMPETENSI KEPRIBADIAN GURU PADA SEKOLAH MENENGAH KEJURUAN (SMK) KOSGORO 2 PAYAKUMBUH - Thiara Zamhir (Jurnal Bahana Manajemen Pendidikan, 2014)
This research is the personal competence of teachers in vocational Kosgoro 2 Payakumbuh that is still not running as it should be. The purpose of this research was to obtain information about 1) personal competence of teachers who act in accordance with the norms of religious, social and cultural.2) personal competence of teachers who present themselves as being honest, noble, role models for students and community 3) personality that present themselves as being steady, stable, wise and authoritative 4) personality that have a work ethic, high responsibility, a sense of proud in being a teacher. 5) personal competence of teachers who uphold the code of ethics of the teaching profession. This study is designed as a descriptive study. The Total population in this study as many as 687 people. Samples were taken by the purposive sampling technique with a number of 88 people. Thus, it can be said that the Student Perceptions of the Teacher Personality Competence on SMK Kosgoro 2 Payakumbuh needs to be improved. Key words: Teacher Personality